The Lifestyle-Dependent Microbial Interactions Vary Between Upstream and Downstream of the Three Gorges Dam - Wang, Shang; Hou, Weiguo; Jiang, Hongchen; Dong, Hailiang; Huang, Liuqin; Chen, Shu; Wang, Bin; Chen, Yongcan; Lin, Binliang; Deng, Ye (Frontiers in Ecology and Evolution, 2021)
Dams represent the most significant anthropogenic disturbance to global rivers. Previous studies have shown that free-living and particle-attached microbes exhibited differentially in river and reservoir ecosystems. However, little is known about dam effect on their co-occurrence patterns. Here, a random matrix theory (RMT)-based network approach was used to construct microbial ecological networks for free-living and particle-attached communities in the immediate vicinity of the Three Gorges Dam (TGD), based on a high-throughput sequencing of 16S rRNA gene. Microbial distribution pattern showed that differences in lifestyle (free-living vs. particle attached) were greater than those caused by geographic position (upstream vs. downstream of the TGD). Network analysis revealed that higher connectivity and lower number of modules in the overall downstream networks. Further considering the lifestyle, the network structures and properties for free-living and particle-attached microbes were different between upstream and downstream of the dam. Specifically, free-living communities located upstream of the dam exhibited more complex co-occurrence pattern than the particle-attached communities, whereas the opposite was true for those downstream of the dam. This variation indicated a strong impact of dam on microbial interactions for microbes with similar lifestyle in the vicinity of dam. We identified 112 persistent OTU-level species which stably coexisted regardless of lifestyle and geographic positions. These persistent species occupied 21.33%-25.57% of the total nodes in each network, and together with their first neighbors they contributed to more than 50% of the nodes and edges to each network. Furthermore, we found taxonomic affiliations for central nodes (with high degree) varied in these persistent species sub-networks. Collectively, our findings expand the current understanding of the dam effect on species interactions variation patterns for free-living and particle-attached communities in the vicinity of the dam, which are more complex than traditional alpha and beta microbial diversity.